2012
DOI: 10.2527/jas.2011-4347
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of in vitro and in situ methods in evaluation of forage digestibility in ruminants1

Abstract: The objective of this study was to compare the application of different in vitro and in situ methods in empirical and mechanistic predictions of in vivo OM digestibility (OMD) and their associations to near-infrared reflectance spectroscopy spectra for a variety of forages. Apparent in vivo OMD of silages made from alfalfa (n = 2), corn (n = 9), corn stover (n = 2), grass (n = 11), whole crops of wheat and barley (n = 8) and red clover (n = 7), and fresh alfalfa (n = 1), grass hays (n = 5), and wheat straws (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 24 publications
2
35
1
1
Order By: Relevance
“…Despite this, EFOS is the recommended laboratory method for whole crop maize in the Nordic feed evaluation system NorFor (Åkerlind et al, 2011). Poor prediction of OMD IN SITU might be due to limitations of enzymes compared to rumen fluid microorganisms used in vitro, in agreement with other recent comparisons in the literature (Koukolová et al, 2004;Jančík et al, 2011;Krizsan et al, 2012). Further, differences between determined in vitro and in vivo digestibility may vary among forage types and species.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Despite this, EFOS is the recommended laboratory method for whole crop maize in the Nordic feed evaluation system NorFor (Åkerlind et al, 2011). Poor prediction of OMD IN SITU might be due to limitations of enzymes compared to rumen fluid microorganisms used in vitro, in agreement with other recent comparisons in the literature (Koukolová et al, 2004;Jančík et al, 2011;Krizsan et al, 2012). Further, differences between determined in vitro and in vivo digestibility may vary among forage types and species.…”
Section: Discussionsupporting
confidence: 86%
“…This is in accordance with previous reports that the VOS method is a good predictor of in vivo OMD . The under-prediction of OMD adapting the VOS technique was greater in this study than what Krizsan et al (2012) found when comparing the predictions with values of in vivo OMD in maize silage samples. The VOS technique has the advantage over other in vitro methods of using smaller amount of rumen fluid and longer incubation period thereby being less sensitive to fluctuations in condition of the inoculum .…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations